Canada, a child's play - Igreja, Miguel Lopes da Costa Prista (2019)
Science4you, a Portuguese developer, producer and seller of scientific and educational toys, leveraged the worldwide growth of this category to successfully expand its operations abroad. Following a recent entry into the United States market, the purpose of this report is to help the company define the next step in its international expansion. A customized scoring model, based on a set of relevant macro and micro-criteria was developed for Anglo-Saxon and Asian countries, yielding Canada as the market with the highest potential. The recommended entry mode is direct exporting via an independent distributor, being complemented with a financial and risk analysis.